PERANCANGAN APLIKASI PERJALANAN DINAS ONLINE YAYASAN PENDIDIKAN TELKOM - Gilang Gemilang Ramadhan Putra; Ari Purno Wahyu (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
The business trip in Telkom Education Foundantion is one of the trips that should be conducted by the staff upon the request made by the board of directors/executives/head of the institution/head of unit that includes any trip meant for duties, training, seminar, conference, comparative study, visitation, and special duty. The operational process at YPT was still using a printed letter to gain the approval, cost estimation, and the bill approval for the staff. This case brings its own disadvantage, which is human error in calculation. There should be digitalization process knowing that human error in manual processing is higher than the digitalized one. In this study, the writer discussed the design of online business trip application at YPT. A decent design along with proper implementation and accurate testing would create this website-based business trip a positive impact in giving latest innovation at YPT. This would be optimum because the writer used some supportive tools such as CodeIgniter, VS Code, PHPMyadmin, and XAMPP.